2018
DOI: 10.3390/cryst8080321
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nanoscratching Process of GaAs Using Molecular Dynamics

Abstract: In this paper, molecular dynamics method was employed to investigate the nanoscratching process of gallium arsenide (GaAs) in order to gain insights into the material deformation and removal mechanisms in chemical mechanical polishing of GaAs. By analyzing the distribution of hydrostatic pressure and coordination number of GaAs atoms, it was found that phase transformation and amorphization were the dominant deformation mechanisms of GaAs in the scratching process. Furthermore, anisotropic effect in nanoscratc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The study also confirmed that the anisotropy of the surface grain direction had an important influence on the distribution of residual stresses. Yi et al [ 34 ] utilized molecular dynamics to examine GaAs nanoscratching in chemical mechanical polishing. Phase transformation and amorphization were the dominant deformation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The study also confirmed that the anisotropy of the surface grain direction had an important influence on the distribution of residual stresses. Yi et al [ 34 ] utilized molecular dynamics to examine GaAs nanoscratching in chemical mechanical polishing. Phase transformation and amorphization were the dominant deformation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature review, many molecular dynamics (MD) studies were published during the last decade and further studies on nanomachining of GaAs are emerging. These studies shed light on aspects of crack formation [15] during singlepoint diamond turning (SPDT), plastic deformation of GaAs [16], and the material removal mechanism during chemo-mechanical polishing [17]. However, these studies did not address aspects of the size effect observed in GaAs much like the other brittle materials, and they also did not clarify whether the kinetic COF is a sufficiently robust indicator to compare simulations and experiments, especially in this era of the digital twin.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [ 16 ] investigated the ductile response of gallium arsenide by MD simulation and turning experiments. Yi et al [ 17 ] studied the phase transformation and anisotropic of gallium arsenide in nanoscratch process via MD simulation. In this paper, a series of three-dimensional MD simulations are carried out to investigate the ductile deformation in the process of nano-cutting on monocrystalline gallium arsenide.…”
Section: Introductionmentioning
confidence: 99%